The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1136/jnnp-2022-329937
|View full text |Cite
|
Sign up to set email alerts
|

Modified Erasmus GBS Respiratory Insufficiency Score: a simplified clinical tool to predict the risk of mechanical ventilation in Guillain-Barré syndrome

Abstract: BackgroundThis study aimed to determine the clinical and diagnostic factors associated with mechanical ventilation (MV) in Guillain-Barré syndrome (GBS) and to simplify the existing Erasmus GBS Respiratory Insufficiency Score (EGRIS) for predicting the risk of MV.MethodsData from the first 1500 patients included in the prospective International GBS Outcome Study (IGOS) were used. Patients were included across five continents. Patients <6 years and patients from Bangladesh were excluded. Univariable logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…mEGRIS prognostic model : An individual patient's risk of requiring mechanical ventilation can be estimated by using EGRIS 160,161 the updated version of EGRIS, 162 and now with the modified (and simplified) version mEGRIS 159 . An advantage of mEGRIS is that it can be used across the full spectrum of GBS, including mild cases and variants, and in patients from different regions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…mEGRIS prognostic model : An individual patient's risk of requiring mechanical ventilation can be estimated by using EGRIS 160,161 the updated version of EGRIS, 162 and now with the modified (and simplified) version mEGRIS 159 . An advantage of mEGRIS is that it can be used across the full spectrum of GBS, including mild cases and variants, and in patients from different regions.…”
Section: Resultsmentioning
confidence: 99%
“… The TF advises assessing the risk of respiratory failure early in the course of GBS. The TF advises using a prognostic model at hospital admission to quantify the risk of requiring mechanical ventilation. This can be quantified using the modified Erasmus GBS Respiratory Insufficiency Score (mEGRIS) 159 . mEGRIS requires four clinical factors to estimate the risk of requiring mechanical ventilation at any time during the first 2 months from disease onset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher GDS score on admission was a strong predictor for poor outcome at discharge and short-term follow-up, independent of treatment type or in-hospital management (Ruiz-Sandoval and their colleagues) [12]. Luijten and their colleagues found that clinical predictors of the need for mechanical ventilation (MV) were a shorter time from onset of weakness until admission, the presence of facial muscle weakness, bulbar palsy and neck muscle weakness [13].…”
Section: Introductionmentioning
confidence: 99%
“…Number of days between onset of symptoms and nadirMean ± SD (range 1-7 days)3.32 ± 1.64Number of days between onset of weakness and admissionMean ± SD (range) 6.69 ± 4.51(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) Type of antecedent event number = 43 (69.4%)…”
mentioning
confidence: 99%